Kritik Sosial dalam Musik Metal: Analisis Semiotika Lagu ‘God Is a Weapon’ Falling in Reverse - Julita Mustika; Marini Marini (Universitas Sultan Ageng Tirtayasa, 2026)
Enthusiasm for metal music in Indonesia has grown since the 1980s, but to this day this genre is still often perceived negatively because it is synonymous with violence, controversy, and dark aesthetics. As a result, the symbolic meaning and social criticism contained in metal music are often overlooked. This research starts from the main problem of the public's lack of understanding of symbols, meaning construction, and social messages in metal music. Therefore, this study aims to uncover the symbolic meanings constructed through lyrics, visuals, and musical elements in metal genre works. The song